2022
DOI: 10.3389/ijph.2022.1605155
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Functional Limitations in Daily Living Among Older Adults in Korea: A Cross-Sectional Study

Abstract: Objective: This paper assesses the relationship between demographics, health parameters, and functional limitations among older adults in Korea, including limitations in activities of daily living (ADLs) and instrumental activities of daily living (IADLs).Methods: We analyzed data from the Korean Longitudinal Study of Aging survey in 2020 and included only participants aged 65 and older. Multinomial logistic regression models were conducted to evaluate the factors that predicted functional limitations.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In agreement with findings in population-based studies [ 29 30 ], our results indicated that low physical activity was a contributor to functional disability in older adults. A Mexican cross-sectional study showed that low physical activity was significantly associated with ADL and IADL limitations after adjustment for covariates [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with findings in population-based studies [ 29 30 ], our results indicated that low physical activity was a contributor to functional disability in older adults. A Mexican cross-sectional study showed that low physical activity was significantly associated with ADL and IADL limitations after adjustment for covariates [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…A Mexican cross-sectional study showed that low physical activity was significantly associated with ADL and IADL limitations after adjustment for covariates [ 29 ]. Another research also found that physical inactivity was a factor strongly associated with ADL and IADL functional limitations in older Korean adults [ 30 ]. The contribution of physical activity to functional impairment may be mediated by a positive effect on muscle strength [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, out of the 19 studies that claimed EV based on predictions of functional outcomes, only eight included any type of covariates in their analyses (see Table 2, for details). Yet, it is well recognized that a variety of potential confounds (e.g., age, education, depressive symptoms) correlate both with performance on EF tests (for reviews, see Cortés Pascual et al, 2019; Snyder, 2013) and with daily functioning (Coventry et al, 2020; for review, see Mlinac & Feng, 2016; Nguyen et al, 2022). Thus, correlations between EF tests and IADL performance are meaningless from a practical standpoint, unless they hold after controlling for relevant confounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the 85 + age group, 7.37% of individuals had severe disabilities for ADLs and 12.06% for IADLs. A high rate of mortality was also observed among people who were undereducated, underweight, inactive, depressed, and suffering from three or more chronic diseases [ 9 ]. A study of 49,732 older adults in Japan showed that participation in cultural leisure activities may contribute to improved IADL scores.…”
Section: Discussionmentioning
confidence: 99%